The effect of profitability and debt policy on tax aggressivity with company size as a moderation variable - Vani Vauliyanti; Agus Ismaya Hasanudin; Nurhayati Soleha (Jurnal Mantik, 2023)
This study aims to determine the effect of profitability and debt policy on tax aggressiveness with company size as a moderating variable in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This sample selection used a purposive sampling method so that the samples obtained were 14 food and beverage companies listed on the Indonesian stock exchange in 2018-2022 with a total of 70 observational data for 5 years. The data collection technique used is documentation with source data using secondary data taken through the official website of the Indonesian Stock Exchange. Observation test the hypothesis using multiple linear regression analysis and Moderate Regression Analysis (MRA) with statistical procedures using SPSS software version 26. The results show that profitability has a negative and significant effect on tax aggressiveness, debt policy has a negative effect on tax aggressiveness. Based on the results of the MRA test, firm size cannot moderate profitability on tax aggressiveness and firm size cannot moderate debt policy on tax aggressiveness